The leader peptides of attenuation-regulated chloramphenicol resistance genes inhibit translational termination. - Moffat, J G (1994)
Placing a translation stop codon at the ribosomal pause site in the leader of the attenuation-regulated cat-86 gene activates cat expression in the absence of the inducer, chloramphenicol. Genetic experiments have shown that this phenomenon depends on the amino acid sequence of the leader-encoded peptide and could readily be explained if the peptide was an inhibitor of translation termination. Here we demonstrate that the cat-86 leader pentapeptide is an in vitro inhibitor of translation termination in addition to its previously described antipeptidyltransferase activity.